Functional ankle bandage: Bibliographic review (Cuestiones de Fisioterapia, 2005)
Ankle's taping is commonly used by physiotherapist for treatment and prevention of ankle's sprain.o describes the method and, using a search, get explain the basis of this procedure. Ankle's taping gets reduce the inversion tn the ankle, the appearance of injuries and doesn't limit the usual function in the ankle. Future investigation must analyze the cost-benefit of the procedure and the effects above ankle proprioceptive information.